IMPORTANCE OF TIME MANAGEMENT FOR STUDENTS (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
The aim of the current research was to determine the relationship between the time management skills and academic achievement of the students. However, students' time management can also affect stress level of students as they need to cope with their tasks and their personal achievements. In this regard, the data was collected in order to analyze that how effectively they are managing their time for achieving their academic standards.